PHENOTYPIC STABILITY IN GOSSYPIUM HIRSUTUM L. FOR YIELD, GINNING OUT TURN AND STAPLE LENGTH IN MULTAN COTTON ZONE (Biological Sciences - PJSIR, 1999)
Seed cotton yield, ginning out turn percentage and fibre length data fromsix locations in Multan Zone were evaluated forstability. All these cultivars understudy were stable for ginning out turn percentage in these environments. S-12, MNH93and B557 were identified as the most stable for yield performance. Utilisation of MNH321 was recommended inhybridization to have better stability for ginning out turn percentage. S-12 was identified to be the most stable for staplelength. In conclusion for better stability in yield of seed cotton, ginning out turn percentage and staple length, utilisationof MNH93, B557, MNH321 and S-12 in the breeding programmes are recommended.